Pengaruh Pengendalian Internal, Penerapan Akuntansi Zakat, Transparansi, dan Kompetensi SDM terhadap Akuntabilitas Keuangan - Dwi Vera Usmadyani; Gunawan Aji (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
This study aims to determine the effect of internal control, application of zakat accounting, transparency and competence of human resources on financial accountability. The population in this research are administrators of zakat management organizations in Pekalongan, namely BAZNAS Pekalongan regency, LAZISMU Pekalongan regency, LAZISMU Pekalongan city, LAZIS Jateng Pekalongan, LAZISNU Pekalongan city, and LAZNAS Yatim Mandiri Pekalongan. The sampling technique in this study used the judgment sampling method with a sample of 37 respondents. The type of data used is primary data whose data collection uses a questionnaire. The data analysis technique in this study used multiple linear regression test assisted by SPSS 26.0 program. The results showed that the internal control variable had no effect on financial accountability. The application of zakat accounting variable had no effect on financial accountability. The transparency variable has a positive and significant effect on financial accountability. The human resource competence variable has a positive and significant effect on financial accountability. The results of the F test show that the variables of internal control, application of zakat accounting, transparency and competence of human resources simultaneously have a positive and significant effect on financial accountability with the magnitude of the influence being 88.5%.